2022
DOI: 10.2166/wcc.2022.160
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of historical and future precipitation projections over a diverse topographic region of Khyber Pakhtunkhwa using SDSM

Abstract: This study focuses on the spatio-temporal analysis of rainfall variability, trend patterns, and projected changes using GCM CCSM4 for RCP4.5 and RCP8.5 in Khyber Pakhtunkhwa. The historical rainfall variability (1971–2018), trend, and magnitude were assessed using Mann–Kendall and Spearman's Rho. In addition, to downscale GCMs data of precipitation at the regional level of Khyber Pakhtunkhwa, SDSM conditional sub-model was applied. The monthly Mann–Kendall and Spearman's Rho trend test results revealed that mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…They attributed this to changes in WD frequency. Looking at the Hindu Kush, Rahman et al (2022) reported significantly increasing trends for projected winter precipitation, strongest in the lower-and mid-elevations, in contrast to the recent drying they found in station-based observations for the region. Deng and Ji (2023) also found significant winter wetting of the western Tibetan Plateau in dynamically-downscaled CMIP6 experiments.…”
Section: Changing Impactsmentioning
confidence: 65%
“…They attributed this to changes in WD frequency. Looking at the Hindu Kush, Rahman et al (2022) reported significantly increasing trends for projected winter precipitation, strongest in the lower-and mid-elevations, in contrast to the recent drying they found in station-based observations for the region. Deng and Ji (2023) also found significant winter wetting of the western Tibetan Plateau in dynamically-downscaled CMIP6 experiments.…”
Section: Changing Impactsmentioning
confidence: 65%
“…In meteorological drought the indices mainly depends on the variation in temperature while they ignore the role of temperature and rate of evapotranspiration. The climate change experts predicts the increase in global temperature which ultimately leads to rise the rate of evapotranspiration and drought [ 19 , 36 , 44 ]. Therefore, SPEI drought index has been applied in this study which incorporate both the effect of temperature change taking into account the rate of evapotranspiration and precipitation [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Asian countries including India, Pakistan, Afghanistan, and Sri Lanka have recorded drought in average every three years during the past fifty years [16]. Droughts in Pakistan are common as most of the country experiencing dry climate, with only small area in the north experiencing humid conditions [17][18][19]. Most of the Baluchistan, Sindh and the southern and central parts of Punjab receives less than 250 mm of rainfall annually [17].…”
Section: Introductionmentioning
confidence: 99%